Kolaborasi YAKI dan Mahasiswa KKN Tematik Kelompok 20 dalam Penyuluhan Mitigasi Gempa Bumi di RT 33 Kelurahan Betungan: - Promono, Andreas; sarpeka, Riani; Hidayat, Taufik; Afrianto, Wino; Sucipto, Wahyu; Al Fikri, Naufal Aziz (Jurnal Kewirausahaan & Inovasi, 2025)
This program describes a collaborative effort between the Indonesian Preparedness Action Foundation (YAKI) and Group 20 of Thematic KKN students to conduct earthquake preparedness training for 68 households in RT 33 RW 06 Betungan. The intervention combined YAKI's expertise with student community engagement through risk mapping, evacuation drills, and household mitigation planning. Results showed 85% of participants could identify safe zones and 70% had created family evacuation plans. The partnership model proved effective for delivering targeted disaster education in urban communities.